Method for testing splitting damage of hot mix plant recycled asphalt mixture based on constant force loading

Through the testing method based on Hengli, including constant speed splitting, Hengli split, and multi -stage Hengli damage test, the problem of difficulty in capturing the evolution of the hybrid injury of the heat recycled asphalt mixing material is solved, and the accuracy of the test is improved Evaluation of sexual and damage characteristics.

CN119375026APending Publication Date: 2025-01-28TONGJI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411495842.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing splitting tests are difficult to effectively capture the microevolution process of thermally regenerated asphalt mixture damage, and the material is close to failure when macroscopic cracks appear, making it difficult to observe the process of damage accumulation.

Method used

采用基于恒力加载的厂拌热再生沥青混合料劈裂损伤测试方法,通过恒速劈裂试验、恒力劈裂试验和多阶段恒力损伤试验,获取热再生沥青混合料的劈裂强度、破坏时间和劲度模量,确定损伤拐点以揭示损伤演化规律。

Benefits of technology

By loading through stages, capture the key features of the entire process of damage, improve the accuracy of thermal recycled asphalt mixed material splitting test, and help quickly evaluate the damage behavior and damage characteristics of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119375026A_ABST
    Figure CN119375026A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing splitting damage of a hot mix plant recycled asphalt mixture based on constant force loading, and relates to the field of mixture damage testing. The method is based on constant force loading, ensures that a sample generates continuous and constant damage in the testing process, analyzes the damage evolution law of the thermally recycled asphalt mixture through staged damage loading, finds damage nodes, reveals complex phenomena in damage evolution of the thermally recycled asphalt mixture, and improves the test efficiency. The damage behavior of the material can be quickly evaluated, and the damage characteristics of the thermally recycled asphalt mixture under different environments and load effects can be quantitatively analyzed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of mixture damage testing, and in particular to a method for testing splitting damage of factory-mixed hot-recycled asphalt mixture based on constant force loading. Background Art

[0002] Under the influence of traffic load and environment, damage occurs in asphalt mixture and gradually accumulates. Damage appears in the form of microcracks and eventually develops into macrocracks, which is an important cause of asphalt pavement diseases. According to the different locations of weak surfaces, microcracks can be divided into adhesion damage between asphalt and aggregate and cohesion damage inside asphalt. Hot recycled asphalt mixture forms a complex asphalt-aggregate adhesion interface inside due to the addition of old asphalt and old aggregate, which makes the damage problem more complicated. Existing splitting tests usually adopt a constant speed loading method to evaluate the crack resistance of the mixture by applying a load with a constant displacement rate. During the test, the load gradually increases, the material performance declines, and it is easy to cause rapid damage at the load peak. It is difficult to effectively capture the evolution of micro damage. Moreover, when macro cracks appear during the test, the material is close to destruction, and it is difficult to observe the change process of macro cracks. It can be seen that the existing splitting test is difficult to observe the process of damage accumulation. Summary of the invention

[0003] The purpose of this application is to provide a splitting damage test method for factory-mixed hot-recycled asphalt mixture based on constant force loading, which can realize stage-based damage loading, analyze the damage evolution law of hot-recycled asphalt mixture, explore damage nodes, so as to reveal the complex phenomena in the damage evolution of hot-recycled asphalt mixture and improve the accuracy of splitting damage test of hot-recycled asphalt mixture.

[0004] To achieve the above objectives, this application provides the following solutions:

[0005] In a first aspect, the present application provides a method for testing splitting damage of hot recycled asphalt mixture in a factory based on constant force loading, the testing method comprising:

[0006] Obtain three groups of hot recycled asphalt mixture specimens;

[0007] A constant speed splitting test was conducted on the first group of hot recycled asphalt mixture specimens to obtain the splitting strength of the hot recycled asphalt mixture;

[0008] According to the loading speed of the constant-rate splitting test and the splitting strength of the hot-regenerated asphalt mixture, the constant load is determined, and the constant-force splitting test is carried out on the second group of hot-regenerated asphalt mixture specimens to obtain the failure time of the hot-regenerated asphalt mixture;

[0009] Determine the loading cycle according to the damage time of the hot-regenerated asphalt mixture, conduct a multi-stage constant force damage test on the third group of hot-regenerated asphalt mixture, and obtain the initial stiffness modulus of the hot-regenerated asphalt mixture and the stiffness modulus after each loading;

[0010] The damage inflection point of the hot-regenerated asphalt mixture is determined based on the initial stiffness modulus of the hot-regenerated asphalt mixture and the stiffness modulus after each loading; the damage inflection point is the modulus ratio at the transition point of different damage stages.

[0011] Optionally, according to the loading speed of the constant speed splitting test and the splitting strength of the hot recycled asphalt mixture, a constant load is determined, and a constant force splitting test is performed on the second group of hot recycled asphalt mixture specimens to obtain the failure time of the hot recycled asphalt mixture, specifically including:

[0012] According to the loading speed of the constant speed splitting test and the splitting strength of the hot recycled asphalt mixture, the constant load of the constant force splitting test is set;

[0013] The second group of hot-regenerated asphalt mixture specimens are continuously loaded with the constant load by adaptively adjusting the loading speed of the loading device until the second group of hot-regenerated asphalt mixture specimens completely fail;

[0014] The time difference between the start of loading and complete failure is determined as the failure time.

[0015] Optionally, according to the loading speed of the constant speed splitting test and the splitting strength of the hot recycled asphalt mixture, a constant load of the constant force splitting test is set, specifically including:

[0016] According to the splitting strength of hot recycled asphalt mixture, the maximum load is calculated using the following formula;

[0017] σ t =0.006287P T / h;

[0018] Among them, σ t is the splitting strength (MPa), P T is the maximum load (N), h is the specimen height (mm);

[0019] When the loading speed of the constant-rate splitting test is 1 mm / min, the constant load of the constant-force splitting test is set to 50% of the maximum load;

[0020] When the loading speed of the constant-rate splitting test is 5 mm / min, the constant load of the constant-force splitting test is set to 31% of the maximum load;

[0021] When the loading speed of the constant-rate splitting test is 10 mm / min, the constant load of the constant-force splitting test is set to 24% of the maximum load;

[0022] When the loading speed of the constant-speed splitting test is 30 mm / min, the constant load of the constant-force splitting test is set to 18% of the maximum load;

[0023] When the loading speed of the constant-speed splitting test is 50 mm / min, the constant load of the constant-force splitting test is set to 17% of the maximum load.

[0024] Optionally, the loading cycle is determined according to the damage time of the hot-regenerated asphalt mixture, and a multi-stage constant force damage test is performed on the third group of hot-regenerated asphalt mixture to obtain the initial stiffness modulus of the hot-regenerated asphalt mixture and the stiffness modulus after each loading, specifically including:

[0025] The initial stiffness modulus of the third group of hot recycled asphalt mixture specimens was tested using the indirect tensile stiffness modulus test;

[0026] Determine the loading period to be 15% to 20% of the failure time;

[0027] A multi-stage constant force damage test is performed on the third group of hot-regenerated asphalt mixture specimens according to the loading cycle until the third group of hot-regenerated asphalt mixture specimens are destroyed, and after each unloading, an indirect tensile stiffness modulus test is used to test the stiffness modulus after each loading.

[0028] Optionally, the strain level of the indirect tensile stiffness modulus test is 5.0 μm, the loading rise time is 124 ms, the total duration of each loading cycle is 3000 ms, the preloading number is 10 times, the test loading number is 5 times, and the results are taken as an average of 5 times.

[0029] Optionally, the damage inflection point of the hot-regenerated asphalt mixture is determined according to the initial stiffness modulus of the hot-regenerated asphalt mixture and the stiffness modulus after each loading, specifically including:

[0030] According to the initial stiffness modulus and the stiffness modulus after each loading, the modulus ratio after each loading is calculated;

[0031] According to the modulus ratio after each loading, the modulus decay rate of each loading is calculated;

[0032] A modulus decay rate curve is drawn according to the modulus decay rate of each loading;

[0033] The modulus ratio corresponding to the two end points of the valley region of the modulus decay rate curve is determined as the damage inflection point.

[0034] Optionally, the modulus ratio is calculated as:

[0035]

[0036] Among them, MR iis the modulus ratio after the i-th loading, E i is the stiffness modulus after the i-th loading, and E0 is the initial stiffness modulus.

[0037] Optionally, the modulus decay rate is calculated as:

[0038]

[0039] Among them, MRD i is the modulus decay rate of the i-th loading, MR i+1 is the modulus ratio after the i+1th loading, and ΔT is the loading cycle.

[0040] Optionally, the diameters of the three groups of hot-recycled asphalt mixture specimens are 100 mm, and the heights of the three groups of hot-recycled asphalt mixture specimens are consistent.

[0041] Optionally, before conducting the constant rate splitting test, the constant force splitting test and the multi-stage constant force damage test, the three groups of hot recycled asphalt mixture specimens are kept warm in a constant temperature environmental chamber for at least 5 hours.

[0042] According to the specific embodiments provided in this application, this application discloses the following technical effects:

[0043] The present application provides a splitting damage test method for factory-mixed hot-recycled asphalt mixture based on constant force loading. The method is based on constant force loading to ensure that the sample produces continuous and constant damage during the test process. Through staged damage loading, the key characteristics of the entire damage process are captured, the damage evolution law of the hot-recycled asphalt mixture is analyzed, the damage nodes are explored, and the complex phenomena in the damage evolution of the hot-recycled asphalt mixture are revealed. It is helpful to quickly evaluate the damage behavior of the material and quantitatively analyze the damage characteristics of the hot-recycled asphalt mixture under different environments and loads. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 A flow chart of a method for testing splitting damage of hot recycled asphalt mixture in a factory based on constant force loading provided in one embodiment of the present application;

[0046] Figure 2 A schematic diagram of the splitting strength of hot-regenerated asphalt mixture at different test temperatures provided in one embodiment of the present application;

[0047] Figure 3A schematic diagram of a loading curve for a constant force splitting test provided in an embodiment of the present application;

[0048] Figure 4 A schematic diagram of the failure time at different test temperatures provided in one embodiment of the present application;

[0049] Figure 5 A schematic diagram of the modulus ratio and modulus decay rate in a multi-stage constant force damage test at 5°C provided in an embodiment of the present application;

[0050] Figure 6 A schematic diagram of the modulus ratio and modulus decay rate in a multi-stage constant force damage test at 15°C provided in an embodiment of the present application;

[0051] Figure 7 A schematic diagram of the modulus ratio and modulus decay rate in a multi-stage constant force damage test at 25°C provided in one embodiment of the present application. DETAILED DESCRIPTION

[0052] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0053] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below with reference to the accompanying drawings and specific implementation methods.

[0054] In an exemplary embodiment, Figure 1 As shown, a method for testing the splitting damage of hot recycled asphalt mixture in a factory based on constant force loading is provided, and the testing method includes the following steps 101 to 105. Among them:

[0055] Step 101, obtaining three groups of hot-regenerated asphalt mixture specimens.

[0056] Step 102, performing a constant rate splitting test on the first group of hot-regenerated asphalt mixture specimens to obtain the splitting strength of the hot-regenerated asphalt mixture.

[0057] Step 103, determine the constant load according to the loading speed of the constant speed splitting test and the splitting strength of the hot-regenerated asphalt mixture, perform a constant force splitting test on the second group of hot-regenerated asphalt mixture specimens, and obtain the failure time of the hot-regenerated asphalt mixture.

[0058] Step 104, determining the loading cycle according to the damage time of the hot-regenerated asphalt mixture, performing a multi-stage constant force damage test on the third group of hot-regenerated asphalt mixture, and obtaining the initial stiffness modulus of the hot-regenerated asphalt mixture and the stiffness modulus after each loading.

[0059] Step 105, determining the damage inflection point of the hot-regenerated asphalt mixture according to the initial stiffness modulus of the hot-regenerated asphalt mixture and the stiffness modulus after each loading; the damage inflection point is the modulus ratio at the transition point of different damage stages.

[0060] The test method provided by the above steps 101 to 105 is simple to operate and easy to implement. It can not only obtain specimens with different damage states by means of multi-stage constant force loading, but also quantitatively evaluate the damage state by modulus ratio, thus filling the gap in this field. At the same time, the key damage inflection point in the damage evolution process can also be determined by using the modulus decay rate. This application can evaluate the damage evolution law of hot-regenerated asphalt mixtures containing complex interfaces under different loads and temperatures, and provide a scientific basis for the design and maintenance of roads.

[0061] In another exemplary embodiment, the three groups of hot-regenerated asphalt mixture specimens in step 101 are respectively used for the constant-rate splitting test, the constant-force splitting test, and the multi-stage constant-force damage test. The heights of the three groups of hot-regenerated asphalt mixture specimens differ from the average height by no more than ±0.5 mm, and are kept warm at the target test temperature for at least 5 hours in advance.

[0062] In another exemplary embodiment, step 103 determines a constant load according to the loading speed of the constant rate splitting test and the splitting strength of the hot regenerated asphalt mixture, performs a constant force splitting test on the second group of hot regenerated asphalt mixture specimens, and obtains the failure time of the hot regenerated asphalt mixture, specifically including:

[0063] According to the loading speed of the constant rate splitting test and the splitting strength of the hot-regenerated asphalt mixture, a constant load of the constant force splitting test is set; the second group of hot-regenerated asphalt mixture specimens are continuously loaded with the constant load by adaptively adjusting the loading speed of the loading equipment until the second group of hot-regenerated asphalt mixture specimens completely fail; the time difference between the start of loading and complete failure is determined as the failure time.

[0064] Among them, according to the loading speed of the constant speed splitting test and the splitting strength of the hot recycled asphalt mixture, the constant load of the constant force splitting test is set, specifically including:

[0065] According to the splitting strength of hot recycled asphalt mixture, the maximum load is calculated using the following formula.

[0066] σ t =0.006287P T / h.

[0067] Among them, σ t is the splitting strength, P T is the maximum load and h is the specimen height.

[0068] Further based on the maximum load, a constant load is set according to Table 1.

[0069] Table 1 Constant load of constant force splitting test

[0070] Loading speed of constant speed splitting test (mm / min) 1 5 10 30 50 <![CDATA[Constant load of the constant force splitting test (%P T )]]> 50 31 24 18 17

[0071] In another exemplary embodiment, the loading speed is controlled to be 1 mm / min in the constant speed splitting test.

[0072] In another exemplary embodiment, in the constant force splitting test, the magnitude of the constant load is controlled to be 50% of the maximum load, and the constant load is achieved by adaptively adjusting the loading speed of the loading device.

[0073] In another exemplary embodiment, the intermediate indirect tensile stiffness modulus test is maintained at the same temperature as the splitting test and the damage test, the strain level used is 5.0 μm, the loading rise time is 124 ms, the total duration of each loading cycle is 3000 ms, the pre-loading number is 10 times, the test loading number is 5 times, and the results are taken as the average of 5 times.

[0074] In another exemplary embodiment, the loading cycle of the multi-stage damage test is determined based on the failure time, and a recommended value is 15% to 20% of the failure time.

[0075] In another exemplary embodiment, step 105 specifically includes: calculating the modulus ratio after each loading based on the initial stiffness modulus and the stiffness modulus after each loading; calculating the modulus decay rate of each loading based on the modulus ratio after each loading; drawing a modulus decay rate curve based on the modulus decay rate of each loading; and determining the modulus ratio corresponding to the two endpoints of the valley area of ​​the modulus decay rate curve as the damage inflection point.

[0076] The calculation formula of modulus ratio is:

[0077]

[0078] Among them, MR i is the modulus ratio after the i-th loading, E i is the stiffness modulus after the i-th loading, and E0 is the initial stiffness modulus.

[0079] The calculation formula for modulus decay rate is:

[0080]

[0081] Among them, MRD i is the modulus decay rate of the i-th loading, MR i+1 is the modulus ratio after the i+1th loading, and ΔT is the loading cycle.

[0082] In order to illustrate the specific implementation process of the above test method, the following example is provided.

[0083] Example 1

[0084] The test method provided in the above embodiment is applicable to various factory-mixed hot-recycled asphalt mixtures. In this example, the test temperature is 5°C, and the splitting test, constant force splitting test and multi-stage constant force damage test are all completed at this temperature. Among them, for the splitting test and constant force splitting test, each group of tests were carried out three times in parallel, and the results were averaged. The test object is a hot-recycled asphalt mixture specimen with a RAP dosage of 40%, and the design gradation is AC-16. The new asphalt uses 70# base asphalt (PG64-22), and the asphalt dosage is 2.5%. The specific implementation process is as follows:

[0085] Step (1), prepare three groups of hot recycled asphalt mixture specimens, with a diameter of 100 mm and a height of 50 mm, for splitting test, constant force splitting test and multi-stage constant force damage test respectively, and keep the specimens warm in a constant temperature environment box at 5°C for at least 5 hours in advance.

[0086] Step (2): a constant speed splitting test is performed on the first hot regenerated asphalt mixture specimen of step (1). The loading mode is a mode of controlling the loading speed. The loading speed is maintained at 1 mm / min. The splitting strength is tested. The results are shown in the attached figure. Figure 2 shown.

[0087] Step (3): Based on the splitting strength measured in step (2), a constant force splitting test is performed on the second group of hot regenerated asphalt mixture specimens in step (1). The magnitude of the constant load is 50% of the splitting strength. The constant load is achieved by adaptively adjusting the loading speed of the loading device. The loading is continued until the specimen completely fails and the failure time is determined. The results are shown in the attached figure. Figure 3 and Figure 4 shown.

[0088] Step (4), using the indirect tensile stiffness modulus test, the initial stiffness modulus E0 of the third group of hot-regenerated asphalt mixture specimens in step (1) in the initial state, the strain level adopted in the indirect tensile stiffness modulus test is 5.0μm, the loading rise time is 124ms, the total duration of each loading cycle is 3000ms, the pre-loading number is 10 times, the test loading number is 5 times, and the result is the average value of 5 times.

[0089] Step (5), a multi-stage constant force damage test is performed on the specimen in step (4), the loading cycle is 15% of the damage time in step (3) as a reference, and is finally determined to be 90s. The stiffness modulus E is tested after each unloading. i , until the specimen is destroyed.

[0090] Step (6), the initial stiffness modulus E0 measured according to step (4) and the stiffness modulus E0 after each unloading measured in step (5) i , the modulus ratio MR is calculated using formula (1).

[0091] Step (7), based on the result obtained in step (6), use formula (2) to calculate the modulus decay rate and determine the key damage inflection point.

[0092] At 5°C, the splitting strength of hot recycled asphalt mixture is shown in the attached figure. Figure 2 As shown in the attached figure, the failure time of the specimen in the constant force splitting test is Figure 3 and Figure 4 The modulus ratio and modulus decay rate in the multi-stage constant force damage test are shown in the attached Figure 5 As shown. It can be seen from the results that the modulus decay rate curve is U-shaped and there is a valley range. The modulus ratio of the specimen decays steadily at a low speed within this range, reflecting the stable damage stage of the mixture. In this embodiment, the modulus decay rate in this interval is 0.098% / s to 0.118% / s, and its starting point and end point are the key damage inflection points of the hot-recycled asphalt mixture, corresponding to modulus ratios of 61% and 41%, respectively. This shows that when the modulus ratio is 100% to 61%, it is the deceleration damage stage, when the modulus ratio is 61% to 41%, it is the stable damage stage, and when the modulus ratio is less than 41%, it is the accelerated destruction stage. In addition, from the perspective of duration, the stable damage stage accounts for about 36% of the entire damage process.

[0093] Example 2

[0094] The test method provided in the above embodiment is applicable to various factory-mixed hot-regenerated asphalt mixtures. In this example, the test temperature is 15°C, and the splitting test, constant force splitting test and multi-stage constant force damage test are all completed at this temperature. Among them, for the splitting test and constant force splitting test, each group of tests were carried out three times in parallel, and the results were averaged. The test object is a hot-regenerated asphalt mixture specimen with a RAP dosage of 40%, and the design gradation is AC-16. The new asphalt uses 70# base asphalt (PG64-22), and the asphalt dosage is 2.5%. The specific implementation process is as follows:

[0095] Step (1), prepare three groups of hot recycled asphalt mixture specimens, with a diameter of 100 mm and a height of 50 mm, for constant speed splitting test, constant force splitting test and multi-stage constant force damage test, respectively, and keep the specimens warm in a constant temperature environment box at 15°C for at least 5 hours in advance.

[0096] Step (2): The first group of hot-regenerated asphalt mixture specimens in step (1) were subjected to a constant speed splitting test. The loading mode was a mode of controlling the loading speed. The loading speed was maintained at 1 mm / min. The splitting strength was tested. The results are shown in the attached figure. Figure 2 shown.

[0097] Step (3), according to the splitting strength measured in step (2), the second group of hot regenerated asphalt mixture specimens in step (1) are subjected to a constant force splitting test, the magnitude of the constant load is 50% of the splitting strength, the constant load is achieved by adaptively adjusting the loading speed of the loading device, and the loading is continued until the specimen completely fails, and the failure time is determined. The results are shown in the attached figure. Figure 2 shown.

[0098] Step (4), using the indirect tensile stiffness modulus test, test the initial stiffness modulus E0 of the third group of hot-regenerated asphalt mixture specimens in step (1) in the initial state. The strain level used in the indirect tensile stiffness modulus test is 5.0μm, the loading rise time is 124ms, the total duration of each loading cycle is 3000ms, the pre-loading number is 10 times, the test loading number is 5 times, and the result is the average of 5 times.

[0099] Step (5), a multi-stage constant force damage test is performed on the specimen in step (4), the loading cycle is 15% of the damage time in step (3) as a reference, and is finally determined to be 200s. The stiffness modulus E is tested after each unloading. i , until the specimen is destroyed.

[0100] Step (6), the initial stiffness modulus E0 measured according to step (4) and the stiffness modulus E0 after each unloading measured in step (5) i , the modulus ratio MR is calculated using formula (1).

[0101] Step (7), based on the result obtained in step (6), use formula (2) to calculate the modulus decay rate and determine the key damage inflection point.

[0102] At 15°C, the splitting strength of hot recycled asphalt mixture is shown in the attached figure. Figure 2 As shown in the attached figure, the failure time of the specimen in the constant force splitting test is Figure 3 and Figure 4 The modulus ratio and modulus decay rate in the multi-stage constant force damage test are shown in the attached Figure 6As shown. In this embodiment, the modulus decay rate curve also presents a U-shape, and there is a valley range, and the modulus decay rate is between 0.039% / s and 0.047% / s. Thus, two key damage inflection points of hot-regenerated asphalt mixture can be determined, corresponding to modulus ratios of 60% and 34%, respectively. This shows that when the modulus ratio is 100% to 60%, it is the deceleration damage stage, when the modulus ratio is 60% to 34%, it is the stable damage stage, and when the modulus is lower than 34%, it is the accelerated destruction stage. In addition, from the perspective of duration, the stable damage stage accounts for about 44% of the entire damage process.

[0103] Example 3

[0104] The test method provided in the above embodiment is applicable to various factory-mixed hot-regenerated asphalt mixtures. In this example, the test temperature is 25°C, and the splitting test, constant force splitting test and multi-stage constant force damage test are all completed at this temperature. Among them, for the splitting test and constant force splitting test, each group of tests were carried out three times in parallel, and the results were averaged. The test object is a hot-regenerated asphalt mixture specimen with a RAP dosage of 40%, and the design gradation is AC-16. The new asphalt uses 70# base asphalt (PG64-22), and the asphalt dosage is 2.5%. The specific implementation process is as follows:

[0105] Step (1), prepare three groups of hot recycled asphalt mixture specimens, with a diameter of 100 mm and a height of 50 mm, for splitting test, constant force splitting test and multi-stage constant force damage test respectively, and keep the specimens in a constant temperature environment box at 25°C for at least 5 hours in advance.

[0106] Step (2): The first group of hot-regenerated asphalt mixture specimens in step (1) were subjected to a splitting test. The loading mode was a mode of controlling the loading speed. The loading speed was maintained at 1 mm / min. The splitting strength was tested. The results are shown in the attached figure. Figure 2 shown.

[0107] Step (3): Based on the splitting strength measured in step (2), a constant force splitting test is performed on the second group of hot regenerated asphalt mixture specimens in step (1). The magnitude of the constant load is 50% of the splitting strength. The constant load is achieved by adaptively adjusting the loading speed of the loading device. The loading is continued until the specimen completely fails and the failure time is determined. The results are shown in the attached figure. Figure 3 and Figure 4 shown.

[0108] Step (4), using the indirect tensile stiffness modulus test, the initial stiffness modulus E0 of the third group of hot-regenerated asphalt mixture specimens in step (1) in the initial state, the strain level adopted in the indirect tensile stiffness modulus test is 5.0μm, the loading rise time is 124ms, the total duration of each loading cycle is 3000ms, the pre-loading number is 10 times, the test loading number is 5 times, and the result is the average value of 5 times.

[0109] Step (5), a multi-stage constant force damage test is performed on the specimen in step (4), the loading cycle is 15% of the damage time in step (3) as a reference, and is finally determined to be 220s. The stiffness modulus E is tested after each unloading. i , until the specimen is destroyed.

[0110] Step (6), the initial stiffness modulus E0 measured according to step (4) and the stiffness modulus E0 after each unloading measured in step (5) i , the modulus ratio MR is calculated using formula (1).

[0111] Step (7), based on the result obtained in step (6), use formula (2) to calculate the modulus decay rate and determine the key damage inflection point.

[0112] At 25°C, the splitting strength of hot recycled asphalt mixture is shown in the attached figure. Figure 2 As shown in the attached figure, the failure time of the specimen in the constant force splitting test is Figure 3 and Figure 4 The modulus ratio and modulus decay rate in the multi-stage constant force damage test are shown in the attached Figure 7 As shown. In this embodiment, the modulus decay rate curve is U-shaped, there is a valley range, and the modulus decay rate is between 0.039% / s and 0.048% / s. Thus, two key damage inflection points of hot-regenerated asphalt mixture can be determined, corresponding to modulus ratios of 71% and 31%, respectively. This shows that when the modulus ratio is 100% to 71%, it is the deceleration damage stage, when the modulus ratio is 71% to 31%, it is the stable damage stage, and when the modulus ratio is lower than 31%, it is the accelerated destruction stage. In addition, from the perspective of duration, the stable damage stage accounts for about 62% of the entire damage process.

[0113] The above three embodiments respectively explore the damage characteristics of hot recycled mixture specimens at 5°C, 15°C and 25°C. It can be seen that this method has good applicability for damage evaluation of hot recycled asphalt mixtures at different temperatures. According to the service environment of road materials, selecting appropriate temperatures for damage tests is of great significance for guiding the design and utilization of hot recycled mixtures. Through comprehensive comparison, it is helpful to further understand the influence of temperature on the evolution law of mixture damage.

[0114] from Figure 2 It can be seen that with the increase of test temperature, the splitting strength of hot recycled asphalt mixture shows a downward trend. Among them, the strength decreases by about 50% for every 10°C increase. Therefore, for different temperatures, it is necessary to select a suitable constant load to ensure that the damage evolution process can be effectively captured without excessively extending the time required for the test. Figure 3 and Figure 4It can be seen that as the test temperature increases, the failure time in the constant force splitting test shows an upward trend, and there are significant differences between different temperatures. This shows that the use of 50% of the maximum load as the load level proposed in this application can effectively distinguish the effects of different temperatures on damage.

[0115] from Figure 5 , Figure 6 and Figure 7 It can be seen that under the three test temperatures, the changes in the modulus ratio all show a three-stage rule of "rapid decline, stable decline, and rapid decline again". The modulus decay rate curve is "U" shaped, and the two together reflect the damage evolution characteristics of the mixture. By analyzing the modulus ratio and the modulus decay rate, two key damage inflection points can be determined, corresponding to the modulus ratio when entering the stable damage stage and starting to accelerate development. By comparing the three embodiments, it can be found that the increase in temperature significantly affects the damage evolution characteristics of the mixture, the stable damage stage is advanced, the accelerated damage stage is delayed, and the proportion of the stable damage stage in the total damage increases, reflecting the improvement of the material's damage accumulation capacity.

[0116] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0117] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and core ideas of this application. At the same time, for those skilled in the art, according to the ideas of this application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting this application.

Claims

1. A method for testing the splitting damage of hot recycled asphalt mixture in a factory based on constant force loading, characterized in that: The test method includes: Obtain three groups of hot recycled asphalt mixture specimens; A constant speed splitting test was conducted on the first group of hot recycled asphalt mixture specimens to obtain the splitting strength of the hot recycled asphalt mixture; According to the loading speed of the constant-rate splitting test and the splitting strength of the hot-regenerated asphalt mixture, the constant load is determined, and the constant-force splitting test is carried out on the second group of hot-regenerated asphalt mixture specimens to obtain the failure time of the hot-regenerated asphalt mixture; Determine the loading cycle according to the damage time of the hot-regenerated asphalt mixture, conduct a multi-stage constant force damage test on the third group of hot-regenerated asphalt mixture, and obtain the initial stiffness modulus of the hot-regenerated asphalt mixture and the stiffness modulus after each loading; The damage inflection point of the hot-regenerated asphalt mixture is determined based on the initial stiffness modulus of the hot-regenerated asphalt mixture and the stiffness modulus after each loading; the damage inflection point is the modulus ratio at the transition point of different damage stages.

2. The method for testing splitting damage of hot recycled asphalt mixture in factory based on constant force loading according to claim 1 is characterized in that: According to the loading speed of the constant rate splitting test and the splitting strength of the hot recycled asphalt mixture, the constant load is determined, and the constant force splitting test is carried out on the second group of hot recycled asphalt mixture specimens to obtain the failure time of the hot recycled asphalt mixture, which specifically includes: According to the loading speed of the constant speed splitting test and the splitting strength of the hot recycled asphalt mixture, the constant load of the constant force splitting test is set; The second group of hot-regenerated asphalt mixture specimens are continuously loaded with the constant load by adaptively adjusting the loading speed of the loading device until the second group of hot-regenerated asphalt mixture specimens completely fail; The time difference between the start of loading and complete failure is determined as the failure time.

3. The method for testing splitting damage of hot recycled asphalt mixture in factory based on constant force loading according to claim 2 is characterized in that: According to the loading speed of the constant speed splitting test and the splitting strength of the hot recycled asphalt mixture, the constant load of the constant force splitting test is set, including: According to the splitting strength of hot recycled asphalt mixture, the maximum load is calculated using the following formula; s t =0.006287P T / h; Among them, σ t is the splitting strength, P T is the maximum load, h is the specimen height; When the loading speed of the constant-rate splitting test is 1 mm / min, the constant load of the constant-force splitting test is set to 50% of the maximum load; When the loading speed of the constant-rate splitting test is 5 mm / min, the constant load of the constant-force splitting test is set to 31% of the maximum load; When the loading speed of the constant-rate splitting test is 10 mm / min, the constant load of the constant-force splitting test is set to 24% of the maximum load; When the loading speed of the constant-rate splitting test is 30 mm / min, the constant load of the constant-force splitting test is set to 18% of the maximum load; When the loading speed of the constant-speed splitting test is 50 mm / min, the constant load of the constant-force splitting test is set to 17% of the maximum load.

4. The method for testing splitting damage of hot recycled asphalt mixture in factory based on constant force loading according to claim 1 is characterized in that: The loading cycle is determined according to the damage time of the hot-regenerated asphalt mixture, and a multi-stage constant force damage test is performed on the third group of hot-regenerated asphalt mixture to obtain the initial stiffness modulus of the hot-regenerated asphalt mixture and the stiffness modulus after each loading, specifically including: The initial stiffness modulus of the third group of hot recycled asphalt mixture specimens was tested using the indirect tensile stiffness modulus test; Determine the loading period to be 15% to 20% of the failure time; A multi-stage constant force damage test is performed on the third group of hot-regenerated asphalt mixture specimens according to the loading cycle until the third group of hot-regenerated asphalt mixture specimens are destroyed, and after each unloading, an indirect tensile stiffness modulus test is used to test the stiffness modulus after each loading.

5. The method for testing splitting damage of hot recycled asphalt mixture in factory based on constant force loading according to claim 4 is characterized in that: The strain level of the indirect tensile stiffness modulus test is 5.0 μm, the loading rise time is 124 ms, the total duration of each loading cycle is 3000 ms, the preloading number is 10 times, the test loading number is 5 times, and the results are taken as the average of 5 times.

6. The method for testing splitting damage of hot recycled asphalt mixture in factory based on constant force loading according to claim 1 is characterized in that: According to the initial stiffness modulus of the hot recycled asphalt mixture and the stiffness modulus after each loading, the damage inflection point of the hot recycled asphalt mixture is determined, including: According to the initial stiffness modulus and the stiffness modulus after each loading, the modulus ratio after each loading is calculated; According to the modulus ratio after each loading, the modulus decay rate of each loading is calculated; A modulus decay rate curve is drawn according to the modulus decay rate of each loading; The modulus ratio corresponding to the two end points of the valley region of the modulus decay rate curve is determined as the damage inflection point.

7. The method for testing splitting damage of hot recycled asphalt mixture in factory based on constant force loading according to claim 6 is characterized in that: The modulus ratio is calculated as: Among them, MR i is the modulus ratio after the i-th loading, E i is the stiffness modulus after the i-th loading, and E0 is the initial stiffness modulus.

8. The method for testing splitting damage of hot recycled asphalt mixture in factory based on constant force loading according to claim 6 is characterized in that: The calculation formula for modulus decay rate is: Among them, MRD i is the modulus decay rate of the i-th loading, MR i+1 is the modulus ratio after the i+1th loading, and ΔT is the loading cycle.

9. The method for testing splitting damage of hot recycled asphalt mixture in factory based on constant force loading according to claim 1 is characterized in that: The diameters of the three groups of hot-recycled asphalt mixture specimens are 100 mm, and the heights of the three groups of hot-recycled asphalt mixture specimens are consistent.

10. The method for testing splitting damage of hot recycled asphalt mixture in factory based on constant force loading according to claim 1, characterized in that: Before conducting the constant-rate splitting test, constant-force splitting test and multi-stage constant-force damage test, the three groups of hot-recycled asphalt mixture specimens were kept warm in a constant temperature environmental chamber for at least 5 hours.

Citation Information

Cited By

  • Method and system for identifying and analyzing damage causes of hot recycled asphalt mixture

    CN122283107A